PEMANFAATAN EKSTRAK TANAMAN KETAN HITAM (Oryza sativa Glutinosa) SEBAGAI INDIKATOR ASAM BASA - Hasibuan, Muhammad Arief; Amran, Elva Yasmi; ', Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Research was conducted with the aims to determine pH range, percentage acid base indicator titration error, and stability of Oryza sativa Glutinosa extract as acid base indicator. Oryza sativa Glutinosa grains respectively extracted with maseration using ethanol (HCl 1%). pH range determined by added the extract into buffer solutions pH 1-9. Percentage acid base indicator titration error determined by applied the extract in strong acid-strong base, weak acid-strong base, strong acid-weak base titration. The stability determined by applied the extract in strong acid- strong base titration for 4 (four) months with interval 1 (one) month. The pH range known at 6-7. Percentage acid base indicator titration error were 0,0714 ± 0,0736 % for strong acid-strong base titration, 0,0495 ± 0,0379% for weak acid- strong base, and 3,5635 ± 1,1621% for strong acid-weak base. The stability of the extract shown by small percentage acid base indicator titration error about 0,0803 ± 0,0416%.Keywords : Oryza sativa Glutinosa, Acid Base Indicator, Titration